Conflitos e constrangimentos que cercam a implementação de políticas educacionais voltadas para a equidade: o caso da Escola Plural - Saraiva, Ágnez de Lélis (2007)
This paper analyzed the problems and conflicts generated in the implementation of the Plural School, educational policy of Belo Horizonte in 1995. He showed that this policy was part of a context of reforms that crossed the various nations of Latin America, at a time where educational systems had inefficient and ineffective. And contributed to the creation and deterioration of educational inequalities between rich and poor. The Plural School was considered a policy for equity understood as recognition of the diversity of educational pathways for students. Educational policies for this purpose proved to be difficult to implement, as required changes in the organization of schools and educational systems, changing routines and amplamentes technologies accepted and rooted historicamentes culture of the population. In addition, they identified other variables that could interfere in the implementation process. Were highlighted the design of municipal managers on the implementation process of the Plural School, the way of its implementation, its organization and management model, the distribution of costs and benefits, the conflicts generated and the intensity of them. The analysis found that there was, among the municipal managers of Belo Horizonte, the certainty of the complexity and difficulty of the implementation process of the Plural School and, therefore, mobilized a lot of resources. However, optimism about the reception of the proposal by the school actors led to an underestimation of conflict and resistance to the new educational policy. The management and management model were adequate. But, for generating a high cost on teachers who should be the implementers, the Plural School faced strong resistance of this actor. Among the costs, there is the need for changes in the organization of schools and teaching work routine, causing the sense of loss and consequently various forms of resistance to its implementation. In three schools analyzed changes were identified. In two of the organizational changes were higher and there was a significant rapprochement between your organization and the design of the Plural School. In one, the changes were small and preserved a lot of the traditional model. However, it was realized an adaptation of the design (macro implementation) and how municipal schools have been organizing and implementing the Plural School (micro). The model of organization and routines of the municipal schools of Belo Horizonte have changed in many ways, but preserved much of the model of education that the school Plural sought to combat.